Propriedades físico-quimicas e nutricionais de farinhas mistas de trigo, arroz e soja para elaboração de pães - Wally-Vallim, Ana Paula do Sacramento (2007)
Brazil, for structural conditions and national political is, import great amounts of wheat to use in the bread making. However, Brazil is considered one of the greater producing of soy and rice of the world. This way the use of soy and rice flours for bread making can be considered as a promising alternative for importing reduction of wheat. The aim of the work was study of technological and nutritional effects of the partial substitution of flour wheat for flour mixtures of rice and soy flours. In the study, flours had been valued flour mixtures of rice and defatted soy, were elaborated the fat in the ratios of 90:10, 80:20, 70:30, 60:40 and 50:50 that had substituted the flour of wheat in 10, 20, 30, 40 and 50%. The mixing flours had been chemical evaluated how much to protein texts, carbohydrates, ethereal extract, leached ashes, staple fibers and humidity, sensorially through the parameters of global evaluation and nutritionally through the rocking of nitrogen, biological value, digestibilidade, quotient of proteic efficiency, quotient of liquid proteic, glicemic index, cholesterol and HDL. The results indicate that the substitution of up to 30% of the flour of wheat for equality flour mixture of rice and taken away the fat soy improves the nutritional value of breads, without compromising its technological quality and its sensorial properties.